Notes on an Isolated Population of Brachymeles taylori Brown (Family Scincidae) on an Islet in Bago River, Negros Occidental, Philippines - Alcala, Ely L.; Averia, Leonardo T.; Linaugo, Joji D.; Bucol, Abner A. (Silliman Journal, 2022)
A study of the biodiversity of a small river islet resulted in the discovery of a population of the burrowing skink, Brachymeles taylori Brown (Family Scincidae), in the vegetated portion of the islet. The population density of the species during the rainy season was determined at 4±2.8 (SD) individuals/100m2 or about 800 individuals in the two hectares of forested area with thick humus TPJMBOEEFDBZJOHMFBWFTBOEMPHTPOUIFGPSFTUnPPS5IFTQFDJFT was not observed in the adjacent river banks with Nypa fruticans and/or occupied by a human community. The Pungtod Islet skink population is assumed to have had no contact with other populations of the species for a long time since the geological formation of the islet. The possible genetic differentiation of this population from the other Negros populations of Brachymeles taylori needs to be pursued. The present threats to the species and its microhabitats on the islet are also discussed.